انتهاكات إسرائيل للقانون والاتفاقيات الدولية ضد الأسرى الفلسطينيين داخل السجون الإسرائيلية من منظور دولي - سامر إسماعيل حسن حمودة
This research aims at identifying the implications of Israeli violations of international humanitarian law against Palestinian prisoners inside Israeli prisons. The main problem of the research was the lack of enforcement of international humanitarian laws that are supposed to be binding on Israel to stop the continuous violations against Palestinian prisoners in its prisons. These violations include various forms of physical and psychological torture, as well as infringement of human rights, which are guaranteed by international humanitarian agreements, laws, and divine laws. The research highlights the provisions of international humanitarian law especially the Geneva Conventions on the matter. The research has four main chapters of discussions, including the concepts and scope of international obligation for Israeli violations of the rights of Palestinian prisoners, the forms and nature of the violations, the legal nature of violations of the prisoners' rights, and the rights of Palestinian prisoners under the rules of international law. This research uses a descriptive-analytical approach of data gathered from a variety of sources, including legal documents and the field, to accomplish the study's goals. The research highlights the International Criminal Court as an effective mean to implement and protect the rules of international humanitarian law, including the rights of Palestinian prisoners in Israeli-occupied prisons. Since Palestinian prisoners in occupation prisons are classified as prisoners of war under the Geneva Convention and all international agreements and laws regarding prisoners apply to them, it is regrettable that the International Criminal Court has not been able to stop the repeated violations committed by Israel and its leaders against Palestinian prisoners. This has raised concerns about the effectiveness of the court. In addition to the International Criminal Court, the research reveals that the UN plays a crucial role in pressuring the Israeli government to comply with all international treaties and laws pertaining to prisoners of war that guarantee the protection of prisoners and their rights, including respect for their beliefs, maintenance of their dignity, medical protection and care, and humane treatment.